2014
DOI: 10.1159/000363007
|View full text |Cite
|
Sign up to set email alerts
|

Puerarin Facilitates T-Tubule Development of Murine Embryonic Stem Cell-Derived Cardiomyocytes

Abstract: Aims: The embryonic stem cell-derived cardiomyocytes (ES-CM) is one of the promising cell sources for repopulation of damaged myocardium. However, ES-CMs present immature structure, which impairs their integration with host tissue and functional regeneration. This study used murine ES-CMs as an in vitro model of cardiomyogenesis to elucidate the effect of puerarin, the main compound found in the traditional Chinese medicine the herb Radix puerariae, on t-tubule development of murine ES-CMs. Methods: Electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 31 publications
0
27
1
Order By: Relevance
“…Recent findings disclose new putative drugs that might facilitate accelerated maturation in-vitro like puerarin, a compound found in traditional Chinese medicine [77]. Future studies with hiPS-derived electrocompetent cardiac fibroblasts and biomimetic three-dimensional connective tissue scaffolds may improve the physiological conditions towards a more concise cardiac tissue model.…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings disclose new putative drugs that might facilitate accelerated maturation in-vitro like puerarin, a compound found in traditional Chinese medicine [77]. Future studies with hiPS-derived electrocompetent cardiac fibroblasts and biomimetic three-dimensional connective tissue scaffolds may improve the physiological conditions towards a more concise cardiac tissue model.…”
Section: Discussionmentioning
confidence: 99%
“…Mature miRNAs through pairing to the 3′-untranslated (3′UTR) region to inhibit target genes mRNA translation or promote mRNA degradation [24]. As a class of regulatory molecules, miRNAs participate in many physiological and pathological processes including heart development [25], regeneration [26], hypertrophy [27], contractility [28] and fibrosis [29]. MiRNAs have recently emerged as important regulators of cellular senescence and aging.…”
Section: Mirnasmentioning
confidence: 99%
“…ES cell-derived CMs (ES-CMs) are widely accepted as a promising resource for cell replacement therapy of cardiac disease and a powerful model for investigating the development, maturation as well as pathological remodeling of heart [1-2]. However, accumulating data suggest that current culture system produces primitive ES-CMs with undeveloped structure and contractile function [1, 3-4]. In vivo studies of transplantation of such primitive ES-CMs [5] have shown only partial or transient restoration of heart pumping function.…”
Section: Introductionmentioning
confidence: 99%
“…Accumulated studies have shown that the PI3K/Akt, JAK/STAT, JNK, ERK1/2 and MAPK signaling pathways mediate the bio-effects of puerarin on various types of cells, i.e CMs [2, 17, 20], astrocytes [23], neurons [24], and retinal ganglion cells [10]. Our previous research found that puerarin could enhance the specialization of mES cells into ventricular-like CMs [25], inhibits the proliferation of mES-CMs [2], while improves the t-tubule development of mES-CMs [4], suggesting an ameliorated excitation-contraction coupling of these cells in the presence of puerarin. However, it is still uncertain whether puerarin has effect on the Ca 2+ handling maturation of ES-CMs.…”
Section: Introductionmentioning
confidence: 99%